Test-retest reliability of postural control measures in healthy secondary school pupils: insights from the MOVE12 pilot study - Litleskare, Sigbjørn; Barene, Svein (Frontiers in Sports and Active Living, 2025)
IntroductionPostural control is an essential part of human movement. Measurements of center of pressure displacements by force platform are considered the gold standard for assessing postural control. However, the test-retest reliability of these measurements in field-based conditions is unclear.MethodsThis study aimed to investigate the test-retest reliability of center of pressure measures under field-based conditions, and assess the impact of height, weight, and body mass index (BMI) on test-retest reliability. The study sample comprised 215 upper secondary school pupils (114 girls) aged 16–17 years, all drawn from the control group of a larger intervention study. There was a 12-week interval between the initial test and the retest. Measurements of center of pressure displacements was assessed during a bipedal eyes closed and a unipedal eyes open condition. Interclass correlation coefficients (ICCs) with 95% confidence intervals were calculated for six distinct measures in both conditions. Correlations between the change in postural control and height, weight, and BMI were assessed as well.ResultsTrace length exhibited the best test-retest reliability in both conditions, achieving moderate to good reliability in the bipedal eyes closed condition (ICC = 0.73, 95% CI = 0.66–0.78). Test-retest reliability was higher for all measures in the bipedal eyes closed (ICC's = 0.53–0.73) compared to unipedal eyes open condition, and some of these measures approached zero reliability (ICC's = 0.03–0.48). Among body characteristics, only height was significantly correlated with test-retest changes in postural control (r = 0.16, p < 0.05) and only for two of the measures.DiscussionThis study underscores the necessity of careful selection of postural control measures and thorough assessments in field-based research to achieve acceptable test-retest reliability.